Il salterio commentato di Brunune di Wuerzburg in area slavo-orientale. Fra traduzione e tradizione Con un'appenice di testi - Tomelleri, Vittorio S. (Slavistische Beitraege, 2004)
In the last quarter of the XV. Century was printed in Würzburg the "Expositio Psalmorum", attributed to the Würzburg Bishop Bruno compilation of various commentaries on psalms, biblical odes and other texts ecclesiastical content. One of the first printed editions served as a template for the Russian-Slavonic translation "Tolkovaja Psaltir 'Brunona Gerbipolenskogo", which Dmitrij Gerasimov completed on behalf of the then Novgorod archbishop Makarij in 1535; thanks to the great spread of German prints in Novgorod and the surrounding area, an otherwise quite insignificant psalm commentary was also given special attention in the Eastern Slavs. The aim of this dissertation is to acquaint the "Tolkovaja Psaltir" with the Slavic professional audience, highlighting historical, linguistic and cultural peculiarities that emphasize the importance of this hitherto neglected work, both in terms of the translation problem and in terms of translation on the tradition of lore in the Slavic Orthodox world.